Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect--a decrease in preference for the 20-s delay as its initial link was shortened--was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models, Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement